Analisis Pengaruh Pengungkapan Green Banking Terhadap Kinerja Sustainablity BSI Periode 2021-2025 - Nelfitasari; Rahmi Isriani (LPPM STEI Kanjeng Sepuh Gresik Jawa Timur, 2026)
This study aims to analyze the effect of implementing green banking on sustainability performance at PT Bank Syariah Indonesia (BSI) during the 2021–2025 period. Green banking is understood as a banking strategy that integrates environmental aspects into operations and financing to support sustainable development. The research method uses a quantitative approach with descriptive and associative techniques, based on secondary data from BSI's annual reports and sustainability reports from 2021–2025. The independent variable is green banking, measured through indicators of green financing, eco-friendly operations, green products, and environmental policies. The dependent variable is sustainability performance, reviewed from environmental, social, and economic dimensions. The analysis was conducted using descriptive statistics, Pearson correlation tests, and simple linear regression using Microsoft Excel. The research results show that implementing green banking has a positive impact on BSI's sustainability performance, with improvements in operational efficiency, strengthening social responsibility, and support for achieving sustainability goals. These findings confirm that green banking is an important strategy for Islamic banking in realizing sustainable development while also boosting the company's legitimacy in the eyes of stakeholders.